Gibt es alternative Lösungen zu Check-In-/Check-Out-Systemen? Kontaktlose Chipkarten bei ÖPNV-Verkehrsverbünden. - Holz, Siegfried (Deutscher Verkehrs-Verl., 2006)
Ein Fahrkartensystem, welches nur einen Check-In-Vorgang vom Fahrgast verlangt und auf den Check-Out-Vorgang ganz verzichtet, ermöglicht bereits sehr genaue Daten über die Verkehrsvorgänge von Fahrgästen in ÖPNV-Liniennetzen. difu

Check-In/Check-Out systems are used in many countries. These systems have the advantage that the price of a single journey with Public Transport is calculated at the end of the journey. At this point the correct length of the journey is known. This length is regularly the base of of the ticket price. In Germany CICO-Systems are not used. The PT-user must buy a ticket at the beginning of his journey in the correct distance of the tariff. At the beginning and at the end of the journey there are no registrations of the tickets at access-installations. In the article the results of a study is presented. A ticket system with RFID-smartcards is presented, which operates only with "Check-In"-devices in PT-vehicles. difu
Keywords: Öffentlicher Verkehr; Verkehrsverbund; ÖPNV; S-Bahn; U-Bahn; Verkehrsplanung; Simulation; Fahrkarte; Chipkarte; E-Ticketing; Elektronisches Fahrgeldmanagement